Taxonomic Characterization and Short-Chain Fatty Acids Production of the Obese Microbiota - Martínez-Cuesta, M. Carmen; del Campo, Rosa; Garriga-García, María; Peláez, Carmen; Requena, Teresa (Frontiers in Cellular and Infection Microbiology, 2021)
Intestinal microbiota seems to play a key role in obesity. The impact of the composition and/or functionality of the obesity-associated microbiota have yet to be fully characterized. This work assessed the significance of the taxonomic composition and/or metabolic activity of obese- microbiota by massive 16S rRNA gene sequencing of the faecal microbiome of obese and normoweight individuals. The obese metabolic activity was also assessed by in vitro incubation of obese and normoweight microbiotas in nutritive mediums with different energy content. We found that microbiome richness and diversity of the two groups did not differ significantly, except for Chao1 index, significantly higher in normoweight individuals. At phylum level, neither the abundance of Firmicutes or Bacteroidetes nor their ratio was associated with the body mass index. Besides, the relative proportions in Collinsella, Clostridium XIVa and Catenibacterium were significantly enriched in obese participants while Alistipes, Clostridium sensu stricto, Romboutsia and Oscillibacter were significantly diminished. In regards to metabolic activity, short-chain fatty acids content was significant higher in obese individuals being acetate the most abundant followed by propionate and butyrate. Acetate and butyrate production was also higher when incubating obese microbiota in mediums mimicking diets with different energy content; interestingly, a reduced capability of propionate production was associated to the obese microbiome. In spite of the large interindividual variability, the obese phenotype seems to be defined more by the abundance and/or absence of distinct communities of microorganism rather than by the presence of a specific population.